Perbandingan Royalty Hak Cipta Menjadi Harta Bersama Antara Indonesia dan Malaysia - Maulida Fitriani; Handar Subhandi Bakhtiar (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Copyright royalties as an economic object in intellectual property are of particular concern in family law, especially when associated with their status as joint property in marriage. This study aims to examine and compare how the Indonesian and Malaysian legal systems regulate the distribution of copyright royalties in the context of divorce. In Indonesia, the concept of joint property is regulated in Law Number 1 of 1974, which was updated by Law Number 16 of 2019, as well as in the Compilation of Islamic Law. Meanwhile, in Malaysia, different Islamic family laws between states provide a basis for the division of joint property, including royalties, by considering the contribution of the spouse. This study uses a normative-comparative approach through literature study and analysis of legal documents. It was found that despite the differences in legal systems, both countries in principle recognize copyright royalties as part of joint property if they meet certain requirements, especially regarding the time of acquisition and the contribution of the spouse. This study emphasizes the importance of the principle of justice in the division of intangible assets in the context of a household.